The fragile X syndrome in a large family. III. Investigations on linkage of flanking DNA markers with the fragile site Xq27. - Veenema, H (1987)
In a large family with the fragile X syndrome, we performed linkage investigations with six probes, detecting RFLPs at both sides of the fragile site Xq27. The nearest flanking markers were cX55.7 (DXS105) on the centromeric side (theta = 0.04, lod 5.0) and St14 (DXS52) on the telomeric side (theta = 0.08, lod 4.0). Non-penetrance could be shown by the presence of the grandpaternal X chromosome in three mentally retarded fra(X) positive males. A second non-penetrant male in this family had inherited an abnormal grandmaternal X chromosome. His carrier mother had two retarded fra(X) positive brothers. Intermediate between the non-penetrant and fully penetrant males was a non-retarded male, who expressed the fragile site in 6% of his cells. His X chromosome showed the same polymorphisms as were found in his seven severely retarded brothers. In five fra(X) negative females the presence of an abnormal X chromosome could be demonstrated. Despite the existence of non-penetrance in this pedigree, there was no close linkage between a factor IX polymorphism and the fragile site (theta = 0.16, lod 1.9). However, in six descendants of a non-penetrant male, the change to penetrance appeared to be accompanied by a low recombination frequency for flanking markers.